Survival Rate of Atraumatic Restorative Treatment Restorations in Primary Posterior Teeth in Children with High Risk of Caries in the Republic of Kosovo—1-Year Follow-up - Prokshi, Rina; Gjorgievska, Elizabeta; Prokshi, Brikena; Sopi, Mirlinda; Sejdiu, Miranda (European Journal of Dentistry, 2022)
Objective Atraumatic restorative treatment (ART) may be beneficial for disadvantaged populations with no or limited access to dental services. This study aimed to evaluate the survival rate of single-surface ART restorations in primary posterior teeth in children with high caries risk.Materials and Methods This study was conducted in six rural areas of the Republic of Kosovo, and 100 children aged 3 to 8 years participated in the study. Information was obtained from each parent/guardian regarding their children, such as sociodemographic characteristics, general health, dental history, dietary habits, oral hygiene, and fluoride exposure. The reduced Cariogram was used to estimate the risk of caries in the participants based on the seven factors specified in the program, and all the provided information were collected and entered in a computer program of the Cariogram. A pediatric dentist, accompanied by two assistants, performed 100 ART restorations in school settings using high-viscosity glass-ionomer cement (Fuji IX) following the nine steps of the ART procedure. The restorations were evaluated at 3, 6, 9, and 12 months using the ART restoration criteria.Statistical Analysis Percentages, mean value, standard deviation, mean interquartile range, and difference test between arithmetic mean values were used to analyze the research results.Results Review of the average of reduced Cariogram showed that the majority of children, 72%, were at high risk of developing caries, with only 28% having a good chance of avoiding caries in the future. A total of 77% of the children in the study had never visited dentists before due to poor economic conditions and the lack of dentists in the area. The success rates of ART restorations performed in single-surface cavities in primary teeth were very encouraging, with more than 97% success rates after a 1-year follow-up period.Conclusion Our results demonstrate that ART is efficient, affordable, and practical for the treatment of single-surface cavities in primary posterior teeth. Owing to its low price and atraumatic nature, ART can potentially help disadvantaged children in Kosovo access dental care.
Keywords: atraumatic restorative treatment; disadvantaged populations; glass-ionomer cement; primary teeth